Building effective research policy networks: linking function and form - Mendizabal, Enrique (ODI, 2006)
This paper looks at the factors that affect the key structural charact eristics of research policy networks in an attempt to develop a method ology for studying and understanding what networks do and how. It buil ds on previous work on the roles and functions that networks carry out and focuses on their structural characteristics. The literature on ne tworks is explored to identify the main and most common factors affect ing their structure, and then the paper considers the possible effects of these structural factors on a network's ability to perform one or more of these functions based on some of the lessons learned from a st udy of seven research policy networks in Peru. The paper provides a me nu of factors and characteristics worth considering when intending to build effective networks.